2011
DOI: 10.1007/s00414-011-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Insertion–deletion polymorphisms—utilization on forensic analysis

Abstract: Insertion-deletion (INDEL) markers are very frequent in the human genome and present several advantages for population and forensic studies, such as low mutation rates, easy interpretation, small amplicons, easy genotyping, and the possibility of using multiplex PCR. The great adaptability of INDELs for amplification of low copy number or degraded DNA allows its using as an interesting platform of genetic identity by DNA in forensic cases. In the present study, we tested the ability of 48 diallelic INDEL marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…In several studies, insertion–deletion (INDEL) markers have been used in population genetics and forensics [ 10 12 ] as it is easy to use. In the present study, we used INDEL to describe a unique 40 bp insertion in the HVR- I (control) region that is found mostly in the sambar population from the South India.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, insertion–deletion (INDEL) markers have been used in population genetics and forensics [ 10 12 ] as it is easy to use. In the present study, we used INDEL to describe a unique 40 bp insertion in the HVR- I (control) region that is found mostly in the sambar population from the South India.…”
Section: Discussionmentioning
confidence: 99%
“…As the conventional diallelic Indels have only two alleles per locus, the smaller allele names S or 0, the larger one names L or 1 [10,17]. In this study, there were more than three alleles found for each multi-Indel markers, so it is very necessary to build up an organized nomenclature for the multiallelic Indels.…”
Section: Indel Nomenclaturementioning
confidence: 96%
“…They are widely distributed throughout the genome and derived from single mutation events which occur at a very low frequency. Moreover, some of them might be informative as ancestry markers since they may display significant allele frequency differences among geographically separated populations, whereas others might be a complement in human identification tests [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%